Konsepsi Guru-Guru Pelatih KPLI (Sains) Terhadap Sains, Pengajaran Sains dan Pemelajaran Sains - Filmer Jr , Ivan Douglas; Velu, Jeya (Penerbit Universiti Sains Malaysia, 1994)
The teacher trainees' conceptions toward science, the teaching and learning of science was determined by way of a questionnaire administered at the beginning of the Science Graduate Teaching Diploma course. The responses of 58 respondents were analyzed and four categories of the conceptions of science, two categories of the conceptions of the teaching of science, and four categories of the learning of science were derived. A variety of views were presented because the respondents were graduates of science and engineering from local and foreign institutions who have had some working experience.